Consequences of habitat fragmentation on genetic structure of Chamaedorea alternans (Arecaceae) palm populations in the tropical rain forests of Los Tuxtlas, Veracruz, Mexico - Peñaloza-Ramírez, Juan Manuel; Aguilar-Amezquita, Bernardo; Núñez-Farfán, Juan; Pérez-Nasser, Nidia; Albarrán-Lara, Ana Luisa; Oyama, Ken (Revista mexicana de biodiversidad, 2016)
Chamaedorea alternans is a palm species that has suffered from selective extraction, and habitat loss. We collected 11 populations from fragmented and conserved forest. We assess genetic variation of C. alternans, genetic exchange, differentiation, bottlenecks, effective population size and signals of natural selection. Genetic diversity was higher in conserved than in fragmented forest but not significant. Fragmentation did not play a significant role in genetic diversity, possibly due to the populations heterogeneity. C. alternans has been subject to a pronounced isolation of trees as a product of logging, thus raising inbreeding. Bayesian clustering show a trend towards an increased structuring over the course of generations but also, indicates that populations have recently gone through a bottleneck. The bottleneck following deforestation was not severe enough to lower the effective size, this could lead to high standing genetic diversity, providing a buffer against genetic erosion. We observed directional and balancing selection in C. alternans. Maintenance of variability and increased differentiation signify that their populations have been subject to a differential selective pressure at the ecological and the landscape level, combined effect could lead to disturb pollination and dispersion processes, modifying in the long term the effective population size. Chamaedorea alternans es una especie de palma que ha sufrido extracción selectiva y pérdida del hábitat. Se colectaron 11 poblaciones de bosques fragmentados y conservados. Se calculó la variación genética de C. alternans, intercambio genético, diferenciación, cuellos de botella, el tamaño efectivo y las señales de selección natural. La diversidad genética fue mayor en el bosque conservado que en el fragmentado, pero no fue significativa posiblemente debido a la heterogeneidad de las poblaciones. La fragmentación no ha desempeñado un papel importante en la diversidad genética. C. alternans ha sido objeto de un marcado aislamiento de árboles, elevando así los coeficientes de endogamia. El agrupamiento bayesiano indica una tendencia hacia la estructuración con el curso de las generaciones, incluso, muestra evidencias de poblaciones que han sufrido cuellos de botella. Si el cuello de botella no fue tan severo para reducir el tamaño efectivo, esto pudo resultar en una alta diversidad genética, sirviendo como buffer contra la erosión genética. Observamos selección direccional y balanceadora en C. alternans. La disminución y el mantenimiento de la variabilidad y el aumento de la diferenciación significan que sus poblaciones han sido objeto de una presión diferencial a nivel ecológico y a nivel de paisaje; el efecto combinado podría llevar a alterar los procesos de polinización y dispersión, modificando a largo plazo el tamaño de la población.